Answer:
Step-by-step explanation: put your fraction 6 over 15
![x-5y=-4x-2y](https://tex.z-dn.net/?f=x-5y%3D-4x-2y)
In order to evaluate the given function at x = -3, simply replace "x" in the function with -3 and solve.
![-3-5y=-4(-3)-2y](https://tex.z-dn.net/?f=-3-5y%3D-4%28-3%29-2y)
<em>Multiply -4 and -3 in the function above.</em>
![-3-5y=12-2y](https://tex.z-dn.net/?f=-3-5y%3D12-2y)
<em>Add 3 on both sides of the equation.</em>
![-3-5y+3=12-2y+3](https://tex.z-dn.net/?f=-3-5y%2B3%3D12-2y%2B3)
![-5y=15-2y](https://tex.z-dn.net/?f=-5y%3D15-2y)
<em>Add 2y on both sides of the equation.</em>
![-5y+2y=15-2y+2y](https://tex.z-dn.net/?f=-5y%2B2y%3D15-2y%2B2y)
![-3y=15](https://tex.z-dn.net/?f=-3y%3D15)
<em>Divide both sides of the equation by -3.</em>
![\frac{-3y}{-3}=\frac{15}{-3}](https://tex.z-dn.net/?f=%5Cfrac%7B-3y%7D%7B-3%7D%3D%5Cfrac%7B15%7D%7B-3%7D)
![y=-5](https://tex.z-dn.net/?f=y%3D-5)
Therefore, at x = -3, the value of y = -5. Hence, f(-3) = -5.
Answer:
f(-3) = -5
<em />
ANSWER
See below
EXPLANATION
Given
![f(x) = \frac{ {x}- 9 }{x + 5}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B%20%7Bx%7D-%209%20%7D%7Bx%20%2B%205%7D%20)
and
![g(x) = \frac{ - 5x - 9}{x - 1}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20%20%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20)
![(f \circ \: g)(x)= \frac{ (\frac{ - 5x - 9}{x - 1})- 9 }{(\frac{ - 5x - 9}{x - 1} )+ 5}](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%29-%209%20%7D%7B%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20%29%2B%205%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9(x - 1)}{x - 1}}{\frac{ - 5x - 9 + 5(x - 1)}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209%28x%20-%201%29%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205%28x%20-%201%29%7D%7Bx%20-%201%7D%20%7D%20)
Expand:
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9x + 9}{x - 1}}{\frac{ - 5x - 9 + 5x - 5}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209x%20%20%2B%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205x%20-%205%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9x + 9 - 9}{x - 1}}{\frac{ - 5x + 5x - 5 - 9}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209x%20%20%2B%209%20-%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20%2B%205x%20-%205%20-%209%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 14x }{x - 1}}{\frac{ -14}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%2014x%20%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-14%7D%7Bx%20-%201%7D%20%7D%20)
Since the denominators are the same, they will cancel out,
![(f \circ \: g)(x)= \frac{ - 14x}{ - 14} = x](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%5Cfrac%7B%20-%2014x%7D%7B%20-%2014%7D%20%20%3D%20x)
First add 5 to right side
![\frac{x}{7} = -4+5 = 1](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B7%7D%20%3D%20-4%2B5%20%3D%201)
Next , to cancel the 7, you need to multiply by 7 on both sides
Answer:
7.7 ft
Step-by-step explanation:
The third longest side is also the second shortest side.
The 14 ft side of quadrilateral ABCD corresponds to the 6 ft side of quadrilateral EFGH.
14/6 = 18/x
7/3 = 18/x
7x = 18 * 3
7x = 54
x = 54/7
x = 7.7
Answer: D. 7.7 feet